A Case of Burn Related to Over-Heating of The Cell Phone Battery - Aslan, Fatmagül; Teke, Hacer Yaşar (The Bulletin of Legal Medicine, 2018)
Contemporary communication tools are rather advanced tools, and cell phones have become indispensable parts of our daily lives. The purpose of this case report is to draw attention to new types of forensic cases that could develop in parallel with the advancement of technology and their consequences.35-year-old male’s cell phone battery warmed up and burned his left hand, 2x2 cm sized 2nd degree burn wound with a 1x1 cm bulb area in the middle was found on the left hand palm thenar area.Today, mobile phone technology is the most advanced form of mobile communication in communication technologies. In our country and in the world there is a need for detailed studies dealing with health, communication, social, economic and legal aspects.
Keywords: cell phone; battery; burn; accident